DIRECT AND INDIRECT ILLOCUTIONARY SPEECH ACTS ON DONALD TRUMP’S VICTORY SPEECH IN 2016 - Lanjar Mulyana; Engliana Engliana (INFERENCE: Journal of English Language Teaching, 2021)
This research analyzes direct and indirect illocutionary speech acts on Donald Trump’s 2016 victory speech. This research is a qualitative descriptive study. This research focuses on utterances to analyze the types of illocutionary acts and how they are delivered in speech, directly or indirectly. The results of this study are: (1) there are five types of illocutionary speech acts found in the speech, namely commissive 24%, directive 9.3%, representative 17.3%, expressive 24.6%, and expressive 24.6% and declaration 22.7%. The research findings show that the dominant illocutionary act is an expressive action that is 24.6%. (2) Donald Trump delivers the speech that is mainly conveyed directly